Inbreeding depression in Zebu cattle traits. (19th May 2016) - Pereira, R.J.; Santana, M.L.; Ayres, D.R.; Bignardi, A.B.; Menezes, G.R.O.; Silva, L.O.C.; Machado, C.H.C.; Josahkian, L.A.; Albuquerque, L.G.
Summary: The productivity of herds may be negatively affected by inbreeding depression, and it is important to know how intense is this effect on the livestock performance. We performed a comprehensive analysis involving five Zebu breeds reared in Brazil to estimate inbreeding depression in productive and reproductive traits. Inbreeding depression was estimated for 13 traits by including the individual inbreeding rate as a linear covariate in the standard genetic evaluation models. For all breeds and for almost all traits (no effect was observed on gestation length), the performance of the animals was compromised by an increase in inbreeding. The average inbreeding depression was −0.222% and −0.859% per 1% of inbreeding for linear regression coefficients scaled on the percentage of mean (βm ) and standard deviation (βσ ), respectively. The means for βm (and βσ ) were −0.269% (−1.202%) for weight/growth traits and −0.174% (−0.546%) for reproductive traits. Hence, inbreeding depression is more pronounced in weight/growth traits than in reproductive traits. These findings highlight the need for the management of inbreeding in the respective breeding programmes of the breeds studied here.